(untitled) (The Research of Medical Science Review, 2025)
The biomarkers offer the personalized treatment strategies, real-time monitoring, and early detection. In the era of precision medicine, identifying and validating these biomarkers has great potential to transform cancer therapy. The use of non- invasive biomarkers is very important. Some of the biomarkers are being used efficiently for detecting the early stage of cancers or its progression, nonetheless, there prevails a huge gap in identifying biomarkers with high sensitivity and specificity for effective diagnosis and prognosis of cancer. The biomarkers assisted in the regulation of the normal process through differentiation of the cancerous cells. Protein biomarkers are continuously being researched since they are simple to assess and abundant in the serum of the affected body. Reflectance confocal microscopy and optical coherence tomography are non-invasive methods for diagnosing skin cancers like melanoma. CAR-T cell therapy is used for cancer treatment due to their targeting ability of particular antigens such as glycosylated proteins and epitopes that are expressed on surface of cancerous cells. The most effective cancer biomarkers, regardless of their kind, are straightforward, repeatable, reliable, and affordable detection methods that are linked to quantifiable improvements in patient outcomes.